Fulminant ischaemic colitis with atypical clinical features complicating sickle cell disease. Issue 920 (1st June 2002) - Karim, A; Ahmed, S; Rossoff, L J; Siddiqui, R; Fuchs, A; Multz, A S
Abstract : Clinically significant ischaemic bowel injury is an exceedingly rare complication of sickle cell disease. It manifests as acute surgical abdomen and may respond to conservative treatment. An unusual fatal case of ischaemic colitis with minimal abdominal findings in a young male during a sickle cell vaso-occlusive pain crisis is described. This case demonstrates that an acute surgical abdomen should be considered in such patients who fail to respond to conservative management as untreated this condition may be fatal.